Submerged freshwater plant communities do not show species complementarity effect in wetland mesocosms. (21st December 2018) - Riis, T.; Olesen, A.; Jensen, S. M.; Alnoee, A. B.; Baattrup-Pedersen, A.; Lauridsen, T. L.; Sorrell, B. K.
Abstract : It is a generally accepted theory that ecological functions are enhanced with increased diversity in plant communities due to species complementarity effects. We tested this theory in a mesocosm study using freshwater submerged plant beds to determine if increasing species number caused overyielding and species complementarity. We applied a maximum of four species in the plant beds corresponding to the typical species number in natural freshwater plant beds. We found no clear effects of species number (1–4) on biomass production and thus no conclusive overyielding and complementarity effect. This may be explained by low species differentiation among the four species in plant traits relevant for resource acquisition in freshwater, or that other species interactions, e.g. allelopathy, were inhibiting overyielding. The existing knowledge on species complementarity in aquatic plant communities is sparse and inconclusive and calls for more research.